The Use of Standards on the LADEE Mission. - Gundy-Burlet, Karen (Computer (00189162), 2015)
The Lunar Atmosphere Dust Environment Explorer (LADEE) software developers incorporated IEEE and other standards to achieve high reliability while adhering to strict budget and schedule guidelines.